A Conceptual Model of Islamic Educational Leadership for Managing Constructive Conflict and Strengthening Quality Culture in Madrasahs - Indah Aminatuz Zuhriyah; Siti Aisah; Hidayat Hidayat (Education and Sociedad Journal, 2025)
Leadership practices in many educational settings remain largely authoritarian, limiting the effectiveness of constructive conflict management and hindering the development of an inclusive, quality-oriented institutional culture. This study aims to analyze the leadership practices of madrasah principals in conflict management, reconstructing the meaning of the concept of "giving in does not mean losing" within the framework of constructive conflict management. The research used a qualitative approach with a case study design conducted in a public Islamic elementary school. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using an interactive model. The findings indicate that conflict in madrasahs is multidimensional, encompassing policy, interpersonal, and communication conflicts. Leadership practices based on Islamic values ​​are realized through a "giving in" strategy characterized by active listening, emotional regulation, empathy, and strategic compromise. Constructive conflict management is achieved through a collaborative resolution process that prioritizes mutual understanding and shared goals. Internalization of values-based leadership increases teacher commitment and supports continuous improvement in the quality of learning. This study contributes to the development of values-based educational leadership theory and offers practical insights for madrasah management aligned with global educational and institutional development agendas. It is recommended that future research expand this model to different educational contexts and include quantitative validation to strengthen its generalizability.